Application of the Fixed Effect Model to Measuring Variables Affecting Stock Price in Companies in the Property and Real Estate Industry Sector - Venus F Firdaus; Mohammad Iman Nugroho; Nursina Nursina (Journal of Accounting and Finance Management, 2023)
To determine the effect of company size, price book value, and profitability ratio on stock prices, a comparative causal study was carried out with a sample of 11 property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2017 – 2021 which have complete financial statements. Correlation and regression analysis multiplied using Eviews 9 software. The results of this study indicate that the t test proves that company size has a positive direction but has no effect and is not significant on stock prices. Meanwhile, Price Book Value (PBV) and Profitability Ratios are negative and have no but significant effect on stock prices (share). Research with the F test proves that simultaneously firm size, price book value, and profitability ratios affect stock prices. The coefficient of determination test shows the size of the company, price book value, and the ratio of profitability to stock price of 85.70% while 14.3% is the contribution of other factors.